BABY MASSAGE DAN BABY SWIMMING LEBIH BERPENGARUH DARI BABY MASSAGE DAN BABY GYM TERHADAP KUALITAS TIDUR BAYI USIA 3-6 BULAN - Yelva Febriani; Siti Munawarah (Universitas Fort de Kock Bukittinggi, 2021)
ABSTRAKKualitas tidur bayi sangat berpengaruh pada pertumbuhan bayi. Untuk meningkatkan kualitas tidur bayi dapat dilakukan Baby Massage dan Baby Gym dengan Baby Massage dan Baby Swimming dengan manfaat Membantu mengatasi gangguan tidur sehingga bayi dapat tidur dengan nyaman dan nyenyak. Tujuan penelitian ini untuk mengetahui Perbedaan Pengaruh Baby Massage dan Baby Gym dengan Baby Massage dan Baby Swimming terhadap kualitas tidur bayi usia 3-6 bulan. Desain quasi eksperimen dengan rancangan two group pre test-post test dengan sampel 26 orang bayi berusia 3-6 bulan dengan metode pengambilan sampel yaitu dengan accidental sampling. Hasil rata-rata kualitas tidur bayi sebelum (8 dengan standar deviasi 1,581) dan sesudah (9,77 dengan standar deviasi 1,363) dilakukan pemberian Baby Massage dan Baby Gym dan rata-rata kualitas tidur bayi sebelum (10 dengan standar deviasi 1,826) dan sesudah (12,62 dengan standar deviasi 1,502) dilakukan pemberian Baby Massage dan Baby Swimming. Pengaruh Baby Massage dan Baby Gym dengan Uji t test yaitu mean different sebesar 1,769 dan p value = 0,0001. Pengaruh Baby Massage dan Baby Swimming dengan uji t test yaitu mean different sebesar 2,615 dan p value = 0,0001. Pemberian Baby Massage dan Baby Swimming lebih efektif dengan t hitung adalah 5,059 dengan df = 24 dan p value = 0,0001. Disimpulkan pemberian baby massage dan baby swimming lebih efektif dalam peningkatan kualitas tidur bayi usia 3-6 Bulan. Saran bagi ibu bayi agar untuk seterusnya melakukan pijat bayi secara mandiri untuk memenuhi kebutuhan tidur bayinya dengan menggunakan Baby Massage dan Baby Swimming. Kata kunci : baby gym, baby massage, baby swimming, kualitas tidurABSTRACKThe quality of baby sleep is influential on the baby’s growth. To improve the quality of baby sleep, Baby Massage and Baby Gym with Baby Massage and Baby Swimming can be done. Those treatments give will give benefit for helping to overcome sleep disorders so that babies can sleep comfortably and soundly. The purpose of this study was to determine the difference in the effect of baby massage and baby gym with baby massage and baby swimming on the quality of sleep for infants aged 3-6 months. Quasi experimental design with a two group pre-test-posttest design. Study sample infants at 3-6 months which were divided into 2, the Baby Massage and Baby Gym groups and the Baby Massage and Baby Swimming groups respectively each group consisted of 13 babies. The results of the sleep quality of babies in group I before giving Baby Massage and Baby Gym with an average of 8 with a standard deviation of 1.581 and after giving Baby Massage and Baby Gym with an average of 9.77 with a standard deviation of 1.363. The results of the sleep quality of babies in group I before giving Baby Massage and Baby Swimming with an average of 10 with a standard deviation of 1.826 and after giving Baby Massage and Baby Swimming with an average of 12.62 with a standard deviation of 1.502. The t test results of giving Baby Massage and Baby Gym are mean different of 1.769 and p value = 0.0001. The t test results of giving Baby Massage and Baby Swimming were mean different of 2,615 and p value = 0,0001. The t test results of Baby Massage and Baby Swimming were effective with t count is 5.059 with df = 24 and p value = 0.0001. It is concluded that baby massage and baby gym and baby massage and baby swimming are equally influential in improving the quality of sleep for infants at 3-6 months. From the results of the t test, the baby massage and babyswimming is more effective. Last, it is suggested to mothers’ of the baby to apply baby mothers to continue doing baby massage independently to meet their baby’s sleep needs by using Baby Massage and Baby Swimming. Keywords: Baby Gym, Baby Massage, Baby Swimming, Sleep Quality